Japanese firms in transition responding to the globalization challenge - Roehl, Tom; Bird, Allan (Advances in international management ;, 2004)
The decade long period of slow growth in Japan has raised provocative questions relating to theory development in international management. Japans "lost decade" has led to changes in both overall strategy and to increased variety in individual firm responses to slower growth. The combination of internal changes in the Japanese domestic business environment and external changes in the international environment has generated strong incentives for Japanese firms to seek new ways to structure and compete. These adjustments have necessitated changes not only in the management of Japanese firms domestically, but in overseas markets as well. This volume includes contributing chapters from authors based in Asia, Europe, and North America to examine how Japanese firms have responded to the challenge of a slower domestic economy and a more competitive international economy. Articles were selected to address three aspects of this issue: adaptation to domestic environmental changes, adjustments in inter-organizational relations, and the experience in foreign MNCs in Japan and Japanese MNCs abroad.